The Influence of Media on Interest in Western Culture - Mochamad Rizki Subagja; Muhammad Indrian Willy (Trigin Publisher, 2020)
This study aims to determine the evaluation of the influence of the media on cultural interest in class B students majoring in communication science at the Islamic Nusantara University, this study used a qualitative interview method, where we started by asking the subject questions about western culture and his interest in western culture, then we found Some of the factors that influence it include: Against Human Dignity. Freedom, Creation and Utilization of Technology. Watching from the media, both television and the internet. From the results of this study, we realize that there are many impacts that will occur if we forget about culture and national identity, as well as colonialism ideologically. But it can't be denied either, that there are positive impacts from all of this, namely, such as literacy culture, development of science and the mindset of westerners who tend to think ahead. Students who can pick up good habits in western culture are already able to process the information that comes to them, as evidenced by them only applying good habits such as being punctual, disciplined, throwing garbage in its place and working hard. This will certainly have an impact on their productivity in everyday life, as well as the growing era there are still students who are critical of information and still want to uphold Indonesian culture. throw trash in its place and work hard. This will certainly have an impact on their productivity in everyday life, as well as the growing era there are still students who are critical of information and still want to uphold Indonesian culture. throw trash in its place and work hard. This will certainly have an impact on their productivity in everyday life, as well as the growing era there are still students who are critical of information and still want to uphold Indonesian culture.